Characterization of diffusivity‐based oxygen transport in Arctic organic soil. (15th September 2015) - Chamindu Deepagoda, T. K. K.; Elberling, B.
Summary: Arctic terrestrial ecosystems are characterized by large deposits of near‐surface soil organic carbon in poorly drained areas. Recent changes in Arctic regions such as warming and changes in water balance have adverse effects on the dynamics of near‐surface oxygen, leading to a potential increase in oxidation of near‐surface carbon and emission of CO2 . This study investigated oxygen diffusivity characteristics, in both gaseous and liquid phases, in the upper 10 cm of an organic soil profile from a peatland in Disko, West Greenland (69°N). Two commonly used methods for calculating diffusivity of gaseous‐phase oxygen were applied and discussed to select the most appropriate method for highly porous media, for example peat soil. We measured diffusivity of gaseous‐phase oxygen with a one‐chamber diffusion set‐up in soil at different air contents (mimicking draining), and described it numerically with a previously developed parametric diffusivity model. We obtained precise measurements of liquid‐phase oxygen diffusivity along a depth profile (0–2 cm) in water‐saturated peat soil with a diffusivity microsensor coupled to a micromanipulator. The results show that the choice of an appropriate diffusivity model is critical for predicting oxygen diffusivity in organic soil and that diffusivity in mineral soil is not representative for organic soil. Furthermore, the importance of the non‐linear functionality between water saturation and diffusivity is demonstrated. This highlights the importance of measuring and modelling oxygen diffusivity rather than relying on measurements of observed water content in future studies of CO2 and CH4 dynamics in Arctic soil systems subject to climate changes.